1983
DOI: 10.1111/j.1528-1157.1983.tb04874.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Infantile Spasms: Clinical and Therapeutic Correlations

Abstract: Of 363 infants with infantile spasms (IS) admitted into our hospital during an 18-year period, 286 were closely followed for at least 6 years and form the basis of this report. These patients were divided into symptomatic (165 cases) or cryptogenic (121 cases) groups. The cryptogenic group consisted of patients exhibiting no etiological clues and in whom development until the onset of the disorder was normal, even if some had mild impurities in their previous biography. We did not use the "doubtful subgroup" p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
214
9
18

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 323 publications
(252 citation statements)
references
References 53 publications
11
214
9
18
Order By: Relevance
“…This study included only cryptogenic patients. In a Class III study, early treatment initiation (\1 month following onset of symptoms) in 102 children with cryptogenic spasms, led to improved neurodevelopmental outcome [48]. Favourable cognitive outcome with shorter interval to treatment (\3 weeks [108], \4 weeks [109] and \4 weeks [42]) has also been seen in recent studies including patients with both cryptogenic and symptomatic spasms.…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 90%
See 1 more Smart Citation
“…This study included only cryptogenic patients. In a Class III study, early treatment initiation (\1 month following onset of symptoms) in 102 children with cryptogenic spasms, led to improved neurodevelopmental outcome [48]. Favourable cognitive outcome with shorter interval to treatment (\3 weeks [108], \4 weeks [109] and \4 weeks [42]) has also been seen in recent studies including patients with both cryptogenic and symptomatic spasms.…”
Section: Tuberous Sclerosis (Ts)mentioning
confidence: 90%
“…The common side effects of both drugs are irritability, sleep disturbances and drowsiness [27,39,40,48,66]. Both drugs also have severe side effects.…”
Section: Side Effects Of Corticosteroids and Vigabatrinmentioning
confidence: 99%
“…Others have shown that control of infantile spasms is associated with better development during infancy and childhood [4], [6], [10], [12], [22], [23], [24] and [25]. In a previous report [11], more frequent spasms in children undergoing early surgical intervention were documented.…”
Section: Discussionmentioning
confidence: 99%
“…Our anecdotal experience has been that prednisolone is not as effective in patients with focal or diffuse brain lesions. Because of this, and because previous studies have shown that prednisolone is useful in treating cryptogenic epileptic encephalopathy including infantile spasms, 5,6 we decided to use the drug in patients presenting with normal neuroimaging data and without specific epilepsy etiologies. In the patients with Lennox-Gastaut syndrome (LGS) or early infantile epileptic encephalopathy (EIEE; called ''Otahara syndrome''), seizure attacks had occurred almost every day or at least more than four times a week.…”
Section: Methodsmentioning
confidence: 99%